Prognostic Impact of An Integrative Landscape of Clinical, Immune, and Molecular Features in Non-Metastatic Rectal Cancer - Iseas, Soledad; Sendoya, Juan M.; Robbio, Juan; Coraglio, Mariana; Kujaruk, Mirta; Mikolaitis, Vanesa; Rizzolo, Mariana; Cabanne, Ana; Ruiz, Gonzalo; Salanova, Rubén; Gualdrini, Ubaldo; Méndez, Guillermo; et al. (Frontiers in Oncology, 2022)
Rectal Cancer (RC) is a complex disease that involves highly variable treatment responses. Currently, there is a lack of reliable markers beyond TNM to deliver a personalized treatment in a cancer setting where the goal is a curative treatment. Here, we performed an integrated characterization of the predictive and prognostic role of clinical features mismatch-repair deficiency markers, HER2, CDX2, PD-L1 expression and CD3-CD8+ tumor-infiltrating lymphocytes (TILs) coupled with targeted DNA sequencing of 76 non-metastatic RC patients assigned to total mesorectal excision upfront (TME; n=15) or neoadjuvant chemo-radiotherapy treatment (nCRT; n=61) followed by TME. Ninety-six percent of RC cases displayed mutations affecting cancer driver genes such as TP53, APC, KRAS, ATM, and PIK3CA. Good response to nCRT treatment was observed in approximately 40% of the RC cases, and poor pathological tumor regression was significantly association with worse disease-free survival (DFS, HR=3.45; 95%CI=1.14-10.4; p=0.028). High neutrophils-platelets score (NPS) (OR=10.52; 95%CI=1.34-82.6; p=0.025) and KRAS mutated cases (OR=5.49; 95%CI=1.06-28.4; p=0.042) were identified as independent predictive factors of poor response to nCRT treatment in a multivariate analysis. Furthermore, a Cox proportional-hazard model showed that the KRAS mutational status was an independent prognostic factor associated with higher risk of local recurrence (HR=9.68; 95%CI=1.01-93.2; p<0.05) and shorter DFS (HR=2.55; 95%CI=1.05-6.21; p<0.05), while high CEA serum levels were associated with poor DFS (HR=2.63; 95%CI=1.01-6.85; p<0.05). Integrated clinical and molecular-based unsupervised analysis allowed us to identify two RC prognostic groups (cluster 1 and cluster 2) associated with disease-specific OS (HR=20.64; 95%CI=2.63-162.2; p<0.0001), metastasis-free survival (HR=3.67; 95%CI=1.22-11; p=0.012), local recurrence-free survival (HR=3.34; 95%CI=0.96-11.6; p=0.043) and worse DFS (HR=2.68; 95%CI=1.18-6.06; p=0.012). The worst prognosis cluster 2 was enriched by stage III high-risk clinical tumors, poor responders to nCRT, with low TILs density and high frequency of KRAS and TP53 mutated cases compared with the best prognosis cluster 1 (p<0.05). Overall, this study provides a comprehensive and integrated characterization of non-metastatic RC cases as a new insight to deliver a personalized therapeutic approach.